Gnidia glauca- and Plumbago zeylanica-Mediated Synthesis of Novel Copper Nanoparticles as Promising Antidiabetic Agents - Dhiraj A. Jamdade; Dishantsingh Rajpali; Komal A. Joshi; Rohini Kitture; Anuja S. Kulkarni; Vaishali S. Shinde; Jayesh Bellare; Kaushik R. Babiya; Sougata Ghosh (Hindawi Limited, 2019)
Rapid, eco-friendly, and cost-effective one-pot synthesis of copper nanoparticles is reported here using medicinal plants like Gnidia glauca and Plumbago zeylanica. Aqueous extracts of flower, leaf, and stem of G. glauca and leaves of P. zeylanica were prepared which could effectively reduce Cu2+ ions to CuNPs within 5 h at 100°C which were further characterized using UV-visible spectroscopy, field emission scanning electron microscopy, high-resolution transmission electron microscopy, energy dispersive spectroscopy, dynamic light scattering, X-ray diffraction, and Fourier-transform infrared spectroscopy. Further, the CuNPs were checked for antidiabetic activity using porcine pancreatic α-amylase and α-glucosidase inhibition followed by evaluation of mechanism using circular dichroism spectroscopy. CuNPs were found to be predominantly spherical in nature with a diameter ranging from 1 to 5 nm. The phenolics and flavonoids in the extracts might play a critical role in the synthesis and stabilization process. Significant change in the peak at ∼1095 cm−1 corresponding to C-O-C bond in ether was observed. CuNPs could inhibit porcine pancreatic α-amylase up to 30% to 50%, while they exhibited a more significant inhibition of α-glucosidase from 70% to 88%. The mechanism of enzyme inhibition was attributed due to the conformational change owing to drastic alteration of secondary structure by CuNPs. This is the first study of its kind that provides a strong scientific rationale that phytogenic CuNPs synthesized using G. glauca and P. zeylanica can be considered to develop candidate antidiabetic nanomedicine.